SINTESIS TIO2/ZEOLIT SEBAGAI FOTOKATALIS PADA PENGOLAHAN LIMBAH CAIR INDUSTRI TAPIOKA SECARA ADSORPSI-FOTODEGRADASI - Is Fatimah; Karna Wijaya (Teknoin, 2005)
Research on synthesis of TiO2/Zeolite and Its application as photocatalyst in Tapioca Starch Wastewater Treatment has been investigated. Research conducted by synthesis  of TiO2/zeolite by ion exchange process to exchangeable cations in natural zeolite by Ti4+ solution at varied concentration of 0,12 M, 0, 24 M and 0,48 M followed by oxidation and calcination process, followed characterization by analysis of Ti content, XRD measurement, specific surface area measurement and photoactivity toward methylene blue photodegradation.  TiO2/zeolite photoactivity toward photodegradation of tapioca starch wastewater was tested by exposing photocatalyst-wastewater suspension with UV light in varied time and ratio of photocatalyst weight: volume of wastewater.Result of research showed that TiO2/zeolite  has a photoactivity to decrease COD and cyanide content of tapioca starch wastewater. The photoactivity related to specific surface area and photoactivity toward methylene blue photodegradation physical character and also photodegradation time. The highest photoactivity reached by TiO2/zeolite-1 which is resulted by Ti4+concentration of 0,12 M in the ion exchange process to natural zeolite.Keywords :  zeolite, photocatalyst, wastewater quality